(untitled) (Research, Society and Development, 2022)
Myelomeningocele (MMC) is characterized by a congenital defect in which the baby’s spinal cord does not develop properly, and can be classified as occult, when there is no involvement of the spinal cord, and cystic, when it involves the spinal cord and nerves, thus forming a bump on the baby’s back. For this purpose, qualitative bibliographic research was carried out, in which a survey of scientific documents was carried out in the Scielo, Periodicals Caps, Virtual Health Library and books databases. Through these systems, the following keywords were used: Spina bifida, children, MMC and physiotherapy. With the expected results to expose the importance of physical therapy in motor function in children with this pathology always aiming at a better quality of life and functional independence. Therefore, physiotherapy has developed a role of paramount importance when it comes to rehabilitation in children with motor disorders, such as MMC, offering treatment from birth to adulthood, encouraging the prevention of deformities and sequelae.